MANAJEMEN SISTEM LBB “PROSUS INTEN” JAKARTA SEBAGAI PELOPOR PROGRAM KHUSUS (PROSUS) DENGAN METODE QUANTUM LEARNING - Dikson Silitonga (Lembaga Riset dan Pengabdian Masyarakat Institut Bisnis Nusantara, 2011)
The success of Prosus Inten is not got off of the Inten’s strong and continuous willing itself (Team Learning) to make a developing movement (Learning Organization). Based on the approach system. The success of Inten depends on five basic elements which can not be separated one each other. They are input, transformation process, output, feedback, and environment. By applying The Fifth Disciplines, Inten is going to be Learning Organization, It means that all components will learn continuously, fixing their insufficiency and adopting the era’s need. So, Inten will always survive for any situation and any time.